2012
DOI: 10.1007/978-94-007-4546-9_37
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Heart Rate Control in Patients with Atrial Fibrillation: Impact of Tonic Activation of Peripheral Chemosensory Function in Heart Failure

Abstract: Heart failure (HF) and atrial fibrillation (AF), emerging as two epidemics of the twenty-first century, are commonly associated with each other. Both have been mechanistically linked to changes in cardiac vagal control. The importance of peripheral chemosensors, located in the carotid body, has not been elucidated so far. We therefore investigated whether tonic activation of excitatory chemoreceptor afferents contributes to the altered vagal control in HF patients with a history of AF. In 18 patients (72 ±9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Three tests were used to assess basal autonomic outflow, according to international consensus [ 24 26 ]: 1) Deep breathing test with calculation of the expiratory-inspiratory HR difference (E-I difference) and the expiratory-inspiratory HR ratio (E/I ratio) [ 16 , 27 , 28 ]. 2) Active standing test with calculation of the HR response to postural change (ratio of cycle lengths at beats 15 and 30 after standing; 30/15 ratio) [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three tests were used to assess basal autonomic outflow, according to international consensus [ 24 26 ]: 1) Deep breathing test with calculation of the expiratory-inspiratory HR difference (E-I difference) and the expiratory-inspiratory HR ratio (E/I ratio) [ 16 , 27 , 28 ]. 2) Active standing test with calculation of the HR response to postural change (ratio of cycle lengths at beats 15 and 30 after standing; 30/15 ratio) [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Giannoni et al (2009) [7] found CCS exacerbation in 23% of HF patients who have presented low functional capacity, low parasympathetic nervous activity, as well as high prevalence of paroxysmal atrial fibrillation and ventricular tachycardia. Accordingly, findings in the present study may have been influenced by the exclusion of patients with atrial fibrillation, since previous studies have shown that patients with chemoreflex exacerbation have higher prevalence of atrial fibrillation [16,17], as well as that atrial fibrillation in HF patients may be associated with reduced vagal modulation of HR [16,18], which leads to increased cardiac arrhythmic events [19] and heart failure-associated mortality rates [20].…”
Section: International Journal Of Advanced Engineering Research and Science (Ijaers)mentioning
confidence: 89%
“…HF patients were screened based on echocardiographic examinations performed at local reference centers in cities located in Rio Grande do Sul State, Brazil, from 2014 to 2018. Eighteen (18) assessed chronic obstructive pulmonary disease were excluded from the study [25]. Healthy and physically active individuals reporting smoking habit were also excluded from the study.…”
Section: Samplementioning
confidence: 99%
“…Supporting this, RSA is known to be reduced after atropine application in healthy humans [ 23 , 24 ] and is modulated in diseases such as diabetic autonomic neuropathy [ 25 , 26 ]. Although RSA also depends on feedback regulation such as chemoreceptors [ 27 ] and pulmonary afferents and is further modulated by central respiratory drive [ 28 32 ], the direct cardiac influence and the related decrease in intracardiac vagal control following PVI seem to be key in our patients.…”
Section: Discussionmentioning
confidence: 99%